Strategy and development of organizations in the management of public administration - Cichoń, Seweryn; Knop, Urszula (Management and Administration Journal, 2019)
The development has an overarching character as a concept for creating strategicobjectives and priorities for the organization in public administration. The important role of strategy is wellknown, both in traditional and modern management. The development strategy of the organization in themeaning of public administration takes into account the use of knowledge to analyze current and futureactivities and predicting the possibility of changes occurring in the environment. Knowledge of humanresources management, improvement of methods and tools, enhances the effects of workorganization, relationships and promotes the implementation of previously assumed strategic tasks.Continuous development in the activity of public institutions also affects the external evaluation andcontributes to improving the quality of provided services.